Short Communication: Protein profiles of Giant Mudskipper and its potential use as biomarker candidate for heavy metal contamination in Barito Estuary, Indonesia - HIDAYATURRAHMAH HIDAYATURRAHMAH; MABRUR MABRUR; HERI BUDI SANTOSO; RANI SASMITA; UMMY SHALIHA AULIA RAHMY; BADRUZSAUFARI BADRUZSAUFARI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hidayaturrahmah, Mabrur, Santoso HB, Sasmita R, Rahmy USA, Badruzsaufari. 2019. Short Communication: Protein profiles of Giant Mudskipper and its potential use as biomarker candidate for heavy metal contamination in Barito Estuary, Indonesia. Biodiversitas 20: 745-753. Giant mudskipper (Periphthalmodon schlosseri, Pallas 1770) is one of important biological diversity that potential as bio-indicator in environment assessment which is heavy metal contamination. These fish are susceptible to ambient environment, that effect to their physiological mechanism including protein synthesis and expression. This research aims to identify protein profiles of giant mudskipper muscle and review its potential application as a biomarker for heavy metal contamination in Barito Estuary of South Kalimantan. Total proteins were isolated from fish muscle using Tris EDTA buffer and then precipitated using Ammonium sulfate salt. The protein concentration was measured using Bradford assay and then separated based on molecular weight using the SDS-PAGE method. The result showed muscle proteins of giant mudskipper could be precipitated on optimum condition at Ammonium sulfate saturation 60-70% which protein concentration 5.106 mg.mL-1. The protein separated into 20 bands for raw and precipitated proteins which molecular weight ranging from 33 into 184 kDa. Further study is needed for protein identification based on amino acids sequence of protein bands for biomarker discovery and validation.